LISA: a lean information service architecture for SLA management in multi-cloud environments. (30th April 2021) - Sfondrini, Nicola; Motta, Gianmario
Cloud Computing emerged as a disruptive technology for managing IT services over the internet, evolving from Grid Computing, Utility Computing and Software-as-a-Service (SaaS). After an initial scepticism, international companies are widely migrating their IT workload on private and public Cloud to optimise geographical coverage and launch new digital services. Currently, hybrid and Multi-Cloud environments introduce additional complexity in managing the Quality of Services (QoS) therefore requiring more sophisticated Service Level Agreements (SLAs). To deal with these issues, our research developed a SLA-aware Lean Information Service Architecture (LISA) for managing Multi-Cloud environments that support users in the whole service lifecycle. LISA performance was tested in the Innovation Lab of a global telco operator, by deploying services on private Cloud and public Cloud providers. Experimental results prove not only LISA's effectiveness but also efficiency in various aspects, such as preventing SLA violations and service performance degradations, optimising the QoS, and controlling the service components deployed across multiple public Cloud providers.